Molecular-Genetic Technologies and their places in the Ethyological Diagnosis of the Infectious Combination of Bronchial Asthma - Oksana Kukalo (Global Journal of Clinical Virology - Peertechz Publications, 2019)
The development of the Polymerase Chain Reaction (PCR) method and the implementation of realtime PCR multiplex molecular genetic technologies in the laboratory practice of diagnosing infectious viral diseases have allowed faster and high-sensitivity to detect different etiopathogens directly in clinical specimens.